PERANAN AUDITOR INTERNAL DALAM REVIU LAPORAN KEUANGAN PEMERINTAH DAERAH (SEBUAH PENDEKATAN KUALITATIF) - Giam, Richard Sarmento; Budiarso, Novi Swandari (Universitas Sam Ratulangi, 2021)
Financial reports are a means of communication and accountability of the government to the public. The financial statements are produced from a gov-ernment accounting system, both central and local, in accordance with Government Regulation Number 8 of 2006 concerning Financial Reporting and Performance of Government Agencies, requiring them to be reviewed by the Government Internal Supervisory Apparatus (APIP) before being submitted to the The Audit Board of the Republic of Indonesia (BPK RI) for audit. The Government wants to increase the level of public confidence in the government's performance by obtaining an Unqualified Opinion (WTP) from the results of the examination of the Financial Statements by BPK RI. The data shows that most of the Regional Governments have been able to achieve WTP opinions on LKPD examinations conducted by the BPK, but the facts show that there is a phenomenon where the North Sulawesi Provincial Government has won WTP opinions 7 times consecutively but there are still find-ings from the results. examination of LKPD conducted by BPK, although it has been reviewed by APIP Regional Inspectorate of North Sulawesi Province. This study aims to find out the meaning of APIP's role as an Internal Auditor in carrying out a review of Local Government Financial Reports (LKPD) based on the experience of APIPs involved in implementing LKPD reviews before being submitted to the BPK for examination. This study uses a qualitative method with a phenomenological approach.Â The results of this study indicate that the role of the internal auditor in the review carried out is known to be limited to the fitting of the financial information presented in the Regional Government Financial Report (LKPD) of North Sulawesi Province but is not directly related to the implementation of physical work activities in the field which is often a finding in the audit by BPK Representative of North Sulawesi Province.